Electrocoagulation and Filtration for Brackish Peat Water Desalination - Danial, Mochammmad Meddy; Soeryamassoeka, S.B.; Irmansyah, Fitri; Purnaini, Rizki; Teguh, Rahmat (Jurnal Teknik Sipil, 2024)
Electrocoagulation and filtration have been recognized as effective solutions for water treatment for many years. However, their application in the desalination process remains relatively uncommon. This research will highlight the requirement of systematic investigation into the potential of these processes for effectively reducing salinity levels on brackish water sources. Therefore, this experimental study in a laboratory setting is proposed to explore the efficacy of electrocoagulation combined with filtration in desalinating brackish peat water. The study aims to analyze the performance of these combined treatment processes by measuring key water quality parameters, including salinity and total dissolved solids (TDS), before and after treatment. Through a series of controlled experiments, the effects of varying treatment durations and operational conditions will be assessed to determine optimal parameters for maximum desalination efficiency. By employing advanced statistical analyses, such as ANOVA, this research will rigorously evaluate the effectiveness of the treatment processes. The combination of electrocoagulation (4 hours) and filtration (30 minutes) achieves significant reductions in both salinity and TDS, with a 40% to 83% improvement in water quality. ANOVA confirms these results, showing significant effects (F F-crit, P 0,05). While filtration alone is more effective than electrocoagulation, the combined approach yields even greater contaminant removal, highlighting its superior efficiency.